Penilaian Kerentanan Pantai menggunakan Metode Integrasi CVI-MCA Studi Kasus Pantai Indramayu - Kasim, Faizal; Siregar, Vincentius P. (Forum Geografi, 2012)
The increasing of sea level due to climate change has been focused many research activities in order to know the coastal response to the change, and determine the important variables which have contribution to the coastal change. This paper presents a method for integrating Coastal Vulnerability Index (CVI), Multi Criteria Analysis (MCA) method and Geographic Information-System (GIS) technology to map the coastal vulnerability. The index is calculated based-on six variables: coastal erosion, geomorphology, slope, significant wave height, sea level change and tidal range. Emphasize has been made to the methodological aspect, essentially which is linked to: (i) the use of GIS technique for constructing, interpolation, filtering and resampling the data for shoreline grid, (ii) the standardization each rank of variables (0-1) and the use of several percentile (20%, 40%, 60%, and 80%) for each rank score, and (iii) the use of variableâs rank to map the relative (local) and standard (global) vulnerability of the coastline. The result show that for local, the index consist of four categories: very high (19.61%), high (68.63%), moderate (1,96%), and low (9.80%). Meanwhile, for global level, the index is constantly in low category.